Assessing the appropriateness of prevention and management of venous thromboembolism in Australia: a cross-sectional study. Issue 3 (9th March 2016) - Hibbert, Peter D; Hannaford, Natalie A; Hooper, Tamara D; Hindmarsh, Diane M; Braithwaite, Jeffrey; Ramanathan, Shanthi A; Wickham, Nicholas; Runciman, William B
Abstract : Objectives: The prevention and management of venous thromboembolism (VTE) is often at variance with guidelines. The CareTrack Australia (CTA) study reported that appropriate care (in line with evidence-based or consensus-based guidelines) is being provided for VTE at just over half of eligible encounters. The aim of this paper is to present and discuss the detailed CTA findings for VTE as a baseline for compliance with guidelines at a population level. Setting: The setting was 27 hospitals in 2 states of Australia. Participants: A sample of participants designed to be representative of the Australian population was recruited. Participants who had been admitted overnight during 2009 and/or 2010 were eligible. Of the 1154 CTA participants, 481(42%) were admitted overnight to hospital at least once, comprising 751 admissions. There were 279 females (58%), and the mean age was 64 years. Primary and secondary outcome measures: The primary measure was compliance with indicators of appropriate care for VTE. The indicators were extracted from Australian VTE clinical practice guidelines and ratified by experts. Participants' medical records from 2009 to 2010 were analysed for compliance with 38 VTE indicators. Results: Of the 35 145 CTA encounters, 1078 (3%) were eligible for scoring against VTE indicators. There were 2–84 eligible encounters per indicator at 27 hospitals. Overall compliance with indicators for VTE was 51%, and ranged from 34% to 64% for aggregated sets of indicators. Conclusions: The prevention and management of VTE was appropriate for only half of the at-risk patients in our sample; this provides a baseline for tracking progress nationally. There is a need for national and, ideally, international agreement on clinical standards, indicators and tools to guide, document and monitor care for VTE, and for measures to increase their uptake, particularly where deficiencies have been identified.